Romanticization or Reality: It Ends with Us by Colleen Hoover Through Corpus Stylistics Perspective - Kaonedy, Jesselyn; Istiqomah; Sastia, May; Nasution, Diantry Binarwaty Habibie; Rangkuti, Rahmadsyah (Institut Agama Islam Negeri Ponorogo, 2025)
Corpus stylistics, which involves the analysis of electronic archives of written material, facilitates the understanding of connections between words. This research aims to provide linguistic evidence regarding the genre of Colleen Hoover's popular fiction, It Ends with Us, specifically, to ascertain whether it is a pure romance novel or incorporates aspects of literary realism. A descriptive qualitative approach, grounded in Mahlberg's (2013) corpus stylistics theory, is employed. The primary data for analysis are the four most frequently occurring verbs identified using AntConc. The collocations associated with each verb are subsequently categorized into